The "Rhythmic Fingerprint": An Extension of the nPVI to Quantify Rhythmic Influence - Daniele, Joseph R (Empirical Musicology Review, 2017)
This article is in response to Leigh VanHandel's "The War of the Romantics: An Alternate Hypothesis Using nPVI for the Quantitative Anthropology of Music." (2016) I address comments made in VanHandel's response and propose a new tool, the "rhythmic fingerprint," to move away from representing a composer as a single value (e.g. mean nPVI) and more accurately quantify and classify rhythmic influence within a composer's lifetime.